Um novo sistema de axiomas para a l´ogica paraconsistente J3 (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
We investigate the paraconsistent logic J3. As original result we propose a new sistem of axioms for J3 and present results of soundness and completeness (adequacy) evolving the original three valued matrix semantic for J3.